GRAPE HOUSE - Silva, Bruno (European Scientific Journal, ESJ, 2015)
The present article concerns our will to expand and rebuild a previously assembled building with the purpose of producing, processing and commercializing regional agricultural products. The main focus of this project will be the usage of a terrain with specific agricultural features which will be used not only for private use and consumption but also for exporting/marketing of regional agricultural products. This marketing strategy will be conducted through the amplification and rebuilding of a preexisting stone masonry house located in the plot. In other words, the housing will work as a â€œTasting Houseâ€ for its own agricultural products. The project has one other purpose concerning the advertisement of several other regional manufacturers. In this regard, the project will have its own exhibition site which will subsequently have one other adjacent unit related to agro-tourism activities and a swimming pool, complementing the desired effect on the marketing strategy for the region. The possibilities/philosophy brought by the agro-tourism to the region will allow not only to spread its recognition but also to generate more jobs regarding the agro-cultural production and the maintenance of all the adjacent structures. Note: Currently applying for financial support (PRODER)